2016
DOI: 10.1038/nprot.2016.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of protein aggregation from global fitting of kinetic models

Abstract: The elucidation of the molecular mechanisms by which soluble proteins convert into their amyloid forms is a fundamental prerequisite for understanding and controlling disorders that are linked to protein aggregation, such as Alzheimer's and Parkinson's diseases. However, because of the complexity associated with aggregation reaction networks, the analysis of kinetic data of protein aggregation to obtain the underlying mechanisms represents a complex task. Here we describe a framework, using quantitative kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
1,005
9
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 617 publications
(1,052 citation statements)
references
References 32 publications
36
1,005
9
2
Order By: Relevance
“…It has previously been shown that A␤ fibrils can adopt a pseudotransition state, termed the molten globule state, in which side chain packing at the fiber surface becomes perturbed (22). The molten globule state was defined by a reduction in ThT fluorescence and truncation of the fibrillar structure while the ␤-strand signal was maintained in CD spectroscopy, similar to what we have observed in the presence of DLPC (28). This molten globule state has previously only been observed following treatment of mature aggregates with ultrasonication.…”
Section: Resultssupporting
confidence: 65%
“…It has previously been shown that A␤ fibrils can adopt a pseudotransition state, termed the molten globule state, in which side chain packing at the fiber surface becomes perturbed (22). The molten globule state was defined by a reduction in ThT fluorescence and truncation of the fibrillar structure while the ␤-strand signal was maintained in CD spectroscopy, similar to what we have observed in the presence of DLPC (28). This molten globule state has previously only been observed following treatment of mature aggregates with ultrasonication.…”
Section: Resultssupporting
confidence: 65%
“…2b), for the different kinetic models tested are shown in Fig. 2d-f (Meisl et al 2016a). Two models were most consistent with the data: having either fragmentation or saturated secondary nucleation as the dominant processes of fibril multiplication (Fig.…”
Section: Seeded Kinetic Experimentsmentioning
confidence: 99%
“…Recent intensive research into the physicochemical properties of amyloid and its formation into fibrils in the citoplasm points attention to growth models [3], [29], [38], [31]. In [39] the authors consider the growth of aminoid fibrils and look for a mechanistic explanation of the process in terms of a biochemical reaction network.…”
Section: Fibrillationmentioning
confidence: 99%
“…Let M be the total amount (concentration) of monomer, F be the fibril and C = M -F be the monomer-fibril complex at the time t of aggregation [3], [29], [38], [39]. After aggregation the complex C turns into fibril F , that is, the added monomer molecule M converts into (part of) the fibril F .…”
Section: A a Basic Verhulst-henri Modelmentioning
confidence: 99%